Follow up of civil society to the Quebec Action Plan: Report of Canada: Strengthening of Civil Society Participation: Executive Summary - (:unkn) unknown (My University, 2016)
This Report on Civil Society and Participation in Canada is one part of a 34-month, hemispheric-wide analysis of how well national governments in the Americas are carrying out their democratization promises, made at the 2001 Summit of the Americas in Quebec City.